The analysis of the Russian environmental cooperation with the Arctic Council member states - Němá, Olga (Univerzita Karlova, Fakulta sociálních věd, 2020)
The recently intensifying climate changes enable a large-scale economic development of the Arctic region. This region is characterized by the vast hydrocarbon resources, but also by the unique fragile ecosystem. Therefore, any economic development must be aligned with environmental protection. This protection is encouraged by the leading intergovernmental institution in this area, the Arctic Council. This master thesis aims to analyse Russian environmental cooperation with the Arctic coastal states within the Arctic Council. Its structure follows a theoretical framework, introduced by the liberal intergovernmentalism. Firstly, formation of Russian national Arctic interests is analysed, using the key legal documents. Secondly, Russia's participation in the Arctic Council is studied. Thirdly, bilateral environmental cooperation between Russia and other four Arctic coastal states is analysed. Based on the performed research, the Russian Federation is aware, that reaching its very ambitious plans for economic development of the Arctic is only possible along with improvement of environmental protection. Russia cannot ensure this alone and therefore it actively seeks international cooperation. The research also pointed out, that before the establishment of the Arctic Council, the bilateral cooperation. Aktuálně probíhající klimatické změny umožňují široké ekonomické využití arktického regionu. Tento region je charakterizován rozsáhlými zásobami ropy a zemního plynu, ale také unikátním a zranitelným ekosystémem. Jakékoliv ekonomické využití regionu proto musí být v souladu s ochranou životního prostředí. Tuto ochranu také prosazuje hlavní mezinárodní organizace v regionu, Arktická rada. Cílem této diplomové práce je analyzovat ruskou spolupráci s ostatními členy Arktické rady s přístupem k moři v oblasti ekologie. Struktura práce se řídí teoretickým rámcem vycházejícím z teorie liberálního intergovernmentalismu. Nejdříve je za pomoci klíčových právních dokumentů analyzováno formování ruských národních zájmů v ...